Hyaluronic acid plus heparin for improved efficacy in prevention of adhesion formation in rat uterine horn model - (:unkn) unknown (ELSEVIER SCIENCE BV, 1998)
Objective: To determine the effectiveness of hyaluronic acid (HA) and heparin [unfractioned heparin (UH) or low molecular weight heparin (LMWH)] combination in reducing adhesion formation in a rat uterine horn model. Study Design: Prospective, randomized, comparative study in a rat model was done in Surgical Research Laboratory, Erciyes University. A standard lesion was created by unipolar electrocautery in 120 uterine horns of total 60 female Wistar-Albino rats. Animals were then randomly assigned into four groups, each consisting of 15 animals: (1) control, no adjuvant given, (2) HA, 1 mi of 0.4% solution given onto each horn preoperatively; (3) HA, 1 ml of 0.4% solution given preoperatively plus 1 mi of UH given postoperatively; (4) HA, 1 mi of 0.4% solution given before injury plus 1 ml of LMWH given after injury. A second-look laparotomy was performed two weeks after surgery. The number of horns with adhesion was determined and a scoring system applied. Result(s): The number of horns without adhesion formation was significantly higher in HA plus UH (P<0.05) and HA plus LMWH (P<0.01) groups compared to control group. The extent, severity and total scores of adhesion formation were also found to be significantly reduced in other groups when compared to control group. Combination of HA plus UH and HA plus LMWH significantly reduced all adhesion scores compared to HA alone. But a direct comparison of the ability of HA plus UH versus HA plus LMWH in reducing adhesion scores in the rat uterine horn yielded an insignificant difference. Conclusion: Administration of HA before injury followed by UH or LMWH given after injury has been documented to improve the efficacy of HA alone in reducing adhesion formation. (C) 1998 Elsevier Science Ireland Ltd.
Keywords: adhesion formation; adhesion prevention; hyaluronic acid; heparin; PLASMINOGEN-ACTIVATOR; RABBIT MODEL; MACROPHAGES; INHIBITION